2023
DOI: 10.1667/rade-22-00201.1
|View full text |Cite
|
Sign up to set email alerts
|

RENEB Inter-Laboratory Comparison 2021: The Cytokinesis-Block Micronucleus Assay

Abstract: The goal of the RENEB inter-laboratory comparison 2021 exercise was to simulate a large-scale radiation accident involving a network of biodosimetry labs. Labs were required to perform their analyses using different biodosimetric assays in triage mode scoring and to rapidly report estimated radiation doses to the organizing institution. This article reports the results obtained with the cytokinesis-block micronucleus assay. Three test samples were exposed to blinded doses of 0, 1.2 and 3.5 Gy X-ray doses (240 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Unexpectedly, the point estimates of the doses and their corresponding 95% confidence intervals were systematically higher than the reference doses. The latter could only be revealed due to the high number of participating laboratories and was, interestingly, also observed for other cytogenetic methods (29,42,43). This systematic bias might be introduced due to differences regarding the irradiation or experimental setup between the calibration curves used by the participants and the test samples, by problems during the transport of the samples or by problems with the irradiation setup.…”
Section: Discussionmentioning
confidence: 89%
“…Unexpectedly, the point estimates of the doses and their corresponding 95% confidence intervals were systematically higher than the reference doses. The latter could only be revealed due to the high number of participating laboratories and was, interestingly, also observed for other cytogenetic methods (29,42,43). This systematic bias might be introduced due to differences regarding the irradiation or experimental setup between the calibration curves used by the participants and the test samples, by problems during the transport of the samples or by problems with the irradiation setup.…”
Section: Discussionmentioning
confidence: 89%
“…Using a conversion factor between enamel/air kerma of 6.5 (28), the results agreed well with the air kerma references. Moreover, for cytogenetic assays (DCA, CBMN, FISH and PCC) the dose estimates were systematically higher than the reference doses (26)(27)(28)(29). This systematic shift can partly be attributed to differences in the biological effectiveness between the irradiation sources used for the establishment of calibration curves (mostly 60 Co or 137 Cs gamma rays) and for the exposure of the samples of this ILC (X rays, 240 kVp).…”
Section: Ilc 2021mentioning
confidence: 87%
“…In total 46 organizations from 27 countries participated in the RENEB ILC 2021. Several assays for biological dosimetry (DCA, CBMN, FISH, GE, yH2AX, PCC) and physical retrospective dosimetry (EPR, OSL, TL) were applied (Table 2) and the results for most of the assays are published in a number of papers in this special issue (26)(27)(28)(29)(30)(31). Blood was irradiated in terms of dose in water and various different materials (electronic components and glass from mobile phones, watch glass and mini-biopsies of tooth enamel) were irradiated in terms of air kerma with 0, 1.2 and 3.5 Gy X-ray doses (240 kVp, 1 Gy/min, ;75 keV, 13 mA, HVL ¼ 0.63) at the Bundeswehr Institute of Radiobiology, Munich, Germany and sent to the participating laboratories.…”
Section: Ilc 2021mentioning
confidence: 99%
See 1 more Smart Citation
“…For triage, this is less of an issue for high doses but can affect the lower limit of detection or falsely identify unexposed individuals as exposed. The recent RENEB (Running the European Network of Biological and retrospective physical Dosimetry) exercise showed that semiautomated scoring, where only the Mni-positive BNCs were confirmed, performs better in a blinded interlaboratory comparison [Vral et al, 2023]. CU used a slightly modified semi-automated scoring, with all BNCs automatically identified and imaged and the Mni manually scored in the captured digitized BNC images.…”
Section: Discussionmentioning
confidence: 99%